Circulating Soluble Lectin-Like Oxidized Low-Density Lipoprotein Receptor-1 Levels Are Associated With Erectile Dysfunction in Patients Without Known Coronary Artery Disease - Kobat, Mehmet Ali; Firdolas, Fatih; Balin, Mehmet; Celik, Ahmet; Bentli, Recep; Baydas, Adil (Wiley-Blackwell, 2013)
Aim. Endothelial dysfunction and microvascular damage are involved in the pathogenesis of erectile dysfunction (ED). Soluble lectin-like oxidized low-density lipoprotein receptor-1 (sLOX-1) is identified endothelial receptor for oxidized low-density lipoprotein (ox-LDL) that plays a pivotal role in ox-LDL-induced endothelial dysfunction. The purpose of the current study was to determine the association between sLOX-1 and ED in patients without known coronary artery disease (CAD). Main Outcome Measures. Diagnosis of ED was based on the International Index of Erectile Function Score-5. Levels of sLOX-1 were measured in serum by enzyme-linked immunosorbent assay. Methods. One hundred thirty-eight subjects with ED patients without known CAD (ED group) and 75 age-matched subjects without ED and known CAD (Non-ED Group) were included in this study. Results. Plasma levels of sLOX-1 were significantly higher in ED than in Non-ED group (9587 and 49 +/- 30pg/mL, respectively, P<0.001). The levels of sLOX-1 highly negative correlated with score of ED (r=-0.618, P<0.001). The sLOX-1 levels >75pg/mL predicts ED with 26.8% sensitivity and 96.0% specificity on receiver operator characteristic analysis. Conclusions. Our study demonstrated that serum sLOX-1 levels were associated with endothelial dysfunction that predicts ED. Moreover, the current study revealed that there was strong negative correlation between the levels of circulating sLOX-1 and score of ED. This study suggested sLOX-1 may be involved in the pathogenesis of ED in patients without known CAD. Kobat MA, Frdolas F, Balin M, Celik A, Bentli R, and Baydas A. Circulating soluble lectin-like oxidized low-density lipoprotein receptor-1 levels are associated with erectile dysfunction in patients without known coronary artery disease. J Sex Med 2013;10:2782-2789.
Keywords: Endothelial Function; Erectile Dysfunction; Microvascular Damage; Soluble Lectin-Like Oxidized Low-Density Lipoprotein Receptor-1